Design and development of a web-based science learning tool with a sample unit on particulate nature of matter - Er, Neslihan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
The primary aim of this study is design and development of WEBFEN, a web based science learning tool that follows instructional design guidelines and suggestions derived from current practices of constructivist approach and argumentation method in science education. The tool that is developed and implemented by the researcher using Adobe Flash and ASP.net software platforms includes a variety of interactive learning activities compatible with national science curriculum. It includes three main sections which are student activity, teacher monitoring and administration environments. This tool is designed to help students develop conceptual knowledge on selected unit and also gain argument building skill which is noted as an important element of science education in the literature. As students explore the WebFen, they try to find out evidences for their claims and build up argument statements. The tool also provides various monitoring features for teachers. A review of previous research highlighted the significance of and students’ difficulties on the particulate nature of matter subject. These studies also showed the value of multimedia-based representations in helping students to gain particulate understanding of matter. The particulate nature of matter unit was selected as a sample and learning activities are designed for that topic in the context of present study. The study also includes a preliminary effectiveness study with teachers in order to get feedback and carry out revisions for the tool and a pilot study with students to get initial data on the WebFen’s effectiveness and usability. The results of pilot study showed that students had an improved particulate understanding after using WebFen and that the tool was usable
Keywords: Teaching -- Computer network resources.; World Wide Web.; Science -- Study and teaching -- Computer network resources.; Web-based instruction.